Titanium Dioxide Nanoparticles Modulate Systemic Immune Response and Increase Levels of Reduced Glutathione in Mice after Seven-Week Inhalation - Lehotska Mikusova, Miroslava; Busova, Milena; Tulinska, Jana; Masanova, Vlasta; Liskova, Aurelia; Uhnakova, Iveta; Dusinska, Maria; Krivosikova, Zora; Rollerova, Eva; Alacova, Radka; Wsolova, Ladislava; Horvathova, Mira; et al. (Nanomaterials (Basel, Switzerland), 2023)
Titanium dioxide nanoparticles (TiO2 NPs) are used in a wide range of applications. Although inhalation of NPs is one of the most important toxicologically relevant routes, experimental studies on potential harmful effects of TiO2 NPs using a whole-body inhalation chamber model are rare. In this study, the profile of lymphocyte markers, functional immunoassays, and antioxidant defense markers were analyzed to evaluate the potential adverse effects of seven-week inhalation exposure to two different concentrations of TiO2 NPs (0.00167 and 0.1308 mg TiO2/m3) in mice. A dose-dependent effect of TiO2 NPs on innate immunity was evident in the form of stimulated phagocytic activity of monocytes in low-dose mice and suppressed secretory function of monocytes (IL-18) in high-dose animals. The effect of TiO2 NPs on adaptive immunity, manifested in the spleen by a decrease in the percentage of T-cells, a reduction in T-helper cells, and a dose-dependent decrease in lymphocyte cytokine production, may indicate immunosuppression in exposed mice. The dose-dependent increase in GSH concentration and GSH/GSSG ratio in whole blood demonstrated stimulated antioxidant defense against oxidative stress induced by TiO2 NP exposure.
Keywords: antioxidant defense; lymphocytes; inflammation; cytokines; immune response; titanium dioxide nanoparticles; phagocytic activity and respiratory burst; nanoparticle inhalation; immunotoxicity